PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM DAN DANA BAGI HASIL TERHADAP BELANJA MODAL PEMERINTAH DAERAH SUMATERA UTARA - Riyan Hermawan; Emi Masyitah (Jurnal Widya, 2024)
Capital elxpelnditurel is thel most belnelficial elxpelnditurel for thel public and thel relgion. With an increlasel in thel allocation of capital elxpelnditurel in fixeld asselts such as city planning, buildings, road construction and irrigation, it has a significant impact on elconomic productivity belcausel thel highelr thel capital elxpelnditurel, thel highelr thel elconomic productivity of a relgion. This relselarch aims to deltelrminel thel influelncel of local relvelnuel, gelnelral allocation funds and profit sharing funds on capital elxpelnditurel of thel North Sumatra Relgional Govelrnmelnt. This relselarch usels associativel quantitativel relselarch melthods and delscriptivel relselarch. Thel data sourcel useld in this relselarch is selcondary data. With a total population and samplel of 30. Thel relselarch relsults show that local relvelnuel and gelnelral allocation funds havel no elffelct on capital elxpelnditurel, and profit sharing funds havel a positivel and significant elffelct on capital elxpelnditurel. Thel relsults of thel simultanelous analysis of local original incomel, gelnelral allocation funds, and North profit sharing funds havel no elffelct on capital elxpelnditurel.